Quality Of Tomato As Influenced By Boron And Zinc In Presence Of Different Doses Of Cowdung (Bangladesh Journal of Agricultural Research, 2011)
The experiment was carried out at the Vegetable Research Farm of the Horticulture Research Centre, Bangladesh Agricultural Research Institute, Joydebpur, Gazipur to investigate the effect of boron, zinc, and cowdung on quality of tomato. There were 16 treatments comprising four rates of boron and zinc viz., BoZno. B1.5Zn2 B2Zn4 and B2.5Zn6 kg/ha and four rates of cowdung viz., CDo, CD10, CD15, and CD20 t/ha. Every plot received 253 kg N, 90 kg P, 125 kg K, and 6.6 kg S per hectare. The results reflected that the highest pulp weight (90.24%), dry matter content (5.82%), ascorbic acid (11.2 mg/100g). lycopene content (147 μg/100g), chlorophyll-a (42.0 μg/l00g), chlorophyll-b (61.0 μg/100g), boron content (36 μg/g), zinc content (51 μg /g), marketable fruits at 30 days after storage (74%) and shelf life (17 days) were recorded with the combination of 2.5 kg B/ha + 6 kg Zn/ha, and 20 t/ha cowdung.   Keywords: Quality of tomato; boron; zinc; doses of cowdung. DOI: http://dx.doi.org/10.3329/bjar.v36i1.9239 BJAR 2011; 36(1): 151-163